التجربة الروائية عند عبد الفتاح كيليطو " نماذج مختارة " - نادية مداوي (My University, 2023)
summary : We include this research within the framework of revealing the critical issues that harmonized between what is creative, narrative and critical in my novel “Tell me the vision” and “By God, this story is my story” by Kilito, due to its creative and critical value at the same time, as well as because it embraced multiple critical practices, merged with what It is a narrative to give a creative, critical, hybrid being. In addition, the critic imagined criticism through creative practices, and remained faithful to the narrative work of One Thousand and One Nights, which he could not deviate from as a symbol of inspiration in his critical and creative writings. ---------------------------- ملخص : بندرج هذا البحث في إطار الكشف عن القضايا النقدية التي تجانست بين ما هو ابداعي سردي ونقدي في روايتي " انبؤوني بالرؤيا ، " والله إن هذه الحكاية لحكايتي" ، لكيليطو" نظرا لقيمتها الإبداعية والنقدية في الآن نفسه وكذا لأنها احتضنت ممارسات نقدية متعددة، اندمجت مع ما هو سردي لتعطي كائنا إبداعيا نقديا هجينا، فضل عن ذلك قام الناقد بتخييل النقد عبر ممارسات إبداعية، وظل وفيا للعمل السردي ألف ليلة وليلة الذي لم يستطيع أن ينسلخ عنه باعتباره رمزا للإلهام في كتاباته النقدية و الإبداعية ---------------------- résumé : Nous incluons cette recherche dans le cadre de la révélation des enjeux critiques qui s'harmonisent entre ce qui est créatif, narratif et critique dans mon roman "Dis-moi la vision" et "Par Dieu, cette histoire est mon histoire" de Kilito, en raison de son caractère créatif et valeur critique à la fois, ainsi que parce qu'elle embrasse de multiples pratiques critiques, fusionnées avec ce qu'il est narratif pour donner un être créatif, critique, hybride. œuvre des Mille et Une Nuits, dont il ne pouvait s'écarter comme symbole d'inspiration dans ses écrits critiques et créatifs.